Treatment Patterns and Outcomes in a Cohort of Finnish NSCLC Patients with ALK Rearrangement Reflect Rapid Evolution in Treatment Practices - Loponen Heidi; Paajanen Juuso; Vihervaara Ville; Ylä-Viteli Saija; Tamminen Klaus; Torvinen Saku; Jokelainen Jari; Ylisaukko-oja Tero; Silvoniemi Maria (Science PG, 2022)
Background: In Finland approximately 2,500 people are diagnosed with lung cancer annually. A small proportion of non-small cell lung cancer (NSCLC) patients (3–7%) have tumorigenic rearrangement of the anaplastic lymphoma kinase (ALK) gene (ALK-positive). ALK tyrosine kinase inhibitors (TKI) are the standard of care for these patients, showing superior efficacy compared to traditional chemotherapy (CT). Due to the rapid development of novel next-generation ALK TKIs, treatment practices have undergone substantial changes. In Finnish real-life clinical practice the choice of treatment is largely determined by the reimbursement status of available drugs. We set out to assess the prevailing treatment practices and outcomes for NSCLC patients harbouring ALK rearrangement. Materials and methods: This was a retrospective, non-interventional, two-centre study. Adult NSCLC patients from the Hospital District of Southwest Finland and ALK-positive NSCLC patients from the Hospital District of Helsinki and Uusimaa diagnosed between 2013–2017 were included. Patients were followed until death or until the end of study period (May 2018). Data were extracted retrospectively from electronic health records from University Hospital data lakes. Results: A total of 1,260 patients were included, of which 60 were ALK-positive. ALK TKI regimens were mainly received in second and later lines of treatment. Median time-to-next treatment (TTNT) during ALK TKI treatment was 11.0 months (95% CI; 5.0–35.0) and during CT treatment 7.0 months (5.0–11.0) when assessed irrespective of treatment line (p=0.08). Patients who received at least one ALK TKI treatment regimen during the follow-up had median overall survival (OS) of 33.6 months (16.9–NR) from diagnosis vs. 11.5 months (4.6–NR) in patients who were treated with CT regimens only (p=0.054). Conclusions: ALK-positive patients benefit from treatment with ALK targeting agents in real-world clinical practice.